O Brasil no contexto das cadeias globais de valor: um estudo empírico de especialização vertical para os complexos eletroeletrônico e metal mecânico - Rörig, Juliane Regina (2016)
The development of globalization process - especially from the late twentieth century - modified the traditional forms of organization of production and international trade between countries and companies. The major economic importance of transnational companies makes these can resize these traditional forms of production and trade, and implement the so-called Global Value Chains (GVCs), which are based on a bigger fragmentation and international production verticalization, as well as bigger interconnectivity of production and business processes across economies. This study aims to contribute to the analytical and empirical study of insertion segments of the Brazilian industry in GVCs. The study aims to specify the analysis having as object the electro-electronics and mechanical metal complexes, from the Vertical Specialization methodology proposed by Hummels et al (2001) in three periods time cuts 2000, 2005 and 2009. The results showed that Brazil is weakly inserted in GVCs, because it was observed a low value embedded foreign exports (11.62%, 11.04%, 9.22%). Comparing the Brazilian electro-electronics and mechanical metal complexes, it was observed that the contents of both complexes are also low, but the results for the electro-electronics complex (21.39%, 20.36%, 17.53%) were superior to the results from the mechanical metal complex (18.52%, 17.24%, 16.32%). Thus the Brazilian industrial structure is still poorly integrated into the global trade, and in the scope of analysis of the study, the Brazilian electro-electronics manufacturing is the one that most suited to the fragmentation of activities in GVCs.